Peran Moderasi Beragama dalam Memelihara Keharmonisan di Tengah Keberagaman: Pendekatan Tafsir Maqashid Al Qur’an: Pengertian Moderasi Beragama dan Urgensinya dalam Keberagaman, Ayat-Ayat Moderasi melalui Pendekatan Tafsir Maqashid Al Qur’an, Prinsip-Prinsip Moderasi Beragama Antar Umat Beragama, Peran Tafsir terhadap Moderasi Beragama dalam Menjaga Keharmonisan Antar Umat Beragama - Nikmah, Nur Azizatun (Maliki Interdisciplinary Journal, 2025)
This article discusses the role of religious moderation in maintaining harmony amidst diversity, using the maqashid al-Qur’an (objectives of the Qur'an) interpretive approach. The aim of this study is to understand the concept of religious moderation, identify verses that support moderation, and explore the role of maqashid-based interpretation in preserving interreligious harmony. The scope of the research includes the definition of religious moderation, the principles of moderation, and the application of maqashid al-Qur’an interpretation in the context of diversity. The method used is qualitative, with a library research approach by collecting data from primary and secondary sources, while the analysis of verses is conducted through the maqashid al-Qur’an approach. The summary of findings shows that religious moderation, based on maqashid interpretation, plays a significant role in promoting justice, public benefit (maslahah), and balance in religious life. In conclusion, religious moderation is a key to maintaining social harmony. The implications of this research highlight the need to strengthen religious moderation as a foundation for social integration in a pluralistic society.